Assessing the outcome of implementation of jigsaw technique as a learning tool and its effect on performance of 1st year medical students in anatomy - Monika Lalit; Sanjay Piplani (Wolters Kluwer Medknow Publications, 2021)
Introduction: Multiple factors in the contemporaneous trends in curriculum and medical education demand changes in teaching-learning methods with a dramatic change in the paradigm of teacher-centered teaching methods to student-centered learning methods. The jigsaw technique is an active learning methodology that involves active participation by the students in the learning process where they learn by teaching one another. It is an excellent potential tool to grasp an outsized load of information in a brief period or shorter time frame. The objective of the present study was to assess the effectiveness of the implementation of the jigsaw method as a learning tool during a graduate medical education setting. Methodology: The study was conducted among 150 phase I MBBS students during dissection in the department of anatomy. Two topics were decided and taught by didactic lecture. After taking the pretest, the topics were again taught by the jigsaw technique. After completion of the topic with this technique, students' knowledge regarding the topics was judged by taking a posttest. Pre- and postjigsaw technique assessment scores were calculated. The difference in the mean of pre- and posttests was estimated and compared by applying a paired-t-test to know the effectiveness of teaching methods. Results: The difference in the performance of the students in pre- and postjigsaw technique assessment scores test was calculated by applying paired-t-test which was found to be statistically significant (P < 0.001). About 100% of faculty members readily accepted the suggestion of implementing the jigsaw method. About 88% (132) of students showed enthusiasm and interest to take up the activity. Conclusion: There was an eloquent difference in the performance of the students in pretest and posttest knowledge scores. The results indicate a better performance by the students when they are involved actively in learning and found this method very helpful, interesting, and motivating.